2017
DOI: 10.1136/bjophthalmol-2016-309565
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of penetrating keratoplasty in congenital hereditary endothelial dystrophy

Abstract: This study has demonstrated a poor outcome from PKP for CHED in this Irish cohort. This arises from a combination of dense amblyopia and a high risk of graft failure in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
2
9
0
2
Order By: Relevance
“…Other complications were uncommon, with only one case developing endothelial rejection. These outcomes are in contrast to the poor ones reported previously on PK for CHED (Schaumberg et al 1999;€ Ozdemir et al 2012;AlArrayedh et al 2018), whilst are in line with others reported on DSAEK for paediatric eyes (Madi et al 2012;Ramappa et al 2012;Ashar et al 2013aAshar et al , 2013bScorcia et al 2016;Yang et al 2020). Although DMEK is technically feasible in paediatric patients (Mittal et al 2021), it remains our preference to perform DSAEK considering the higher risk of graft detachment in DMEK, which would often require re-bubbling procedures under general anaesthesia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other complications were uncommon, with only one case developing endothelial rejection. These outcomes are in contrast to the poor ones reported previously on PK for CHED (Schaumberg et al 1999;€ Ozdemir et al 2012;AlArrayedh et al 2018), whilst are in line with others reported on DSAEK for paediatric eyes (Madi et al 2012;Ramappa et al 2012;Ashar et al 2013aAshar et al , 2013bScorcia et al 2016;Yang et al 2020). Although DMEK is technically feasible in paediatric patients (Mittal et al 2021), it remains our preference to perform DSAEK considering the higher risk of graft detachment in DMEK, which would often require re-bubbling procedures under general anaesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…2012; AlArrayedh et al. 2018), whilst are in line with others reported on DSAEK for paediatric eyes (Madi et al. 2012; Ramappa et al.…”
Section: Discussionsupporting
confidence: 85%
“…Reforzando la idea de que la especificidad de la indicación es importante para el resultado del trasplante. [20] Se ha observado que los mejores resultados se presentan en pacientes con fines ópticos, como es el caso de las cicatrices u opacidades. El Herpes causa una infección corneal que deja como resultado una opacidad.…”
Section: Estado Del Arteunclassified
“…[10][11][12] However, the trend is shifting towards endothelial keratoplasties over PKP due to various reasons such as suturerelated complications, increased risk of graft rejection and failure, unstable refractive outcomes and need for multiple examinations under anaesthesia in post PKP children. [13][14][15] A study by AlArrayedh et al 16 demonstrated poor outcomes from PKP in CHED due to dense amblyopia and high risk of long-term graft failure. The outcomes of PKP were better when the surgery was done at an older age when compared to the early intervention.…”
Section: Discussionmentioning
confidence: 99%